Introduction to the 34-th international conference on logic programming special issue. Issue 3 (10th August 2018) - DAL PALÙ, ALESSANDRO; TARAU, PAUL
Abstract : This special issue of Theory and Practice of Logic Programming (TPLP) contains the regular papers accepted for presentation at the 34-th International Conference on Logic Programming (ICLP 2018), held in Oxford, United Kingdom, from July 14th to July 17th, 2018.